EKSPLORASI JENIS BURUNG DI KAWASAN KONSERVASI CAGAR ALAM GUNUNG AMBANG PROVINSI SULAWESI UTARA - Diah Irawati Dwi Arini (Pusbindiklat - LIPI, 2010)
A study on the exploration of bird diversity in Gunung Ambang Nature Reserve was performed to collect much information on the existence of the bird species especially the endemic bird species in Wallace bioregion. This research was done by using two methods, an irregular transect method and a method with mistnet installation to determine the bird morphological characteristics. The observation area was determined purposively. A total of68 species has been recorded from this research and those were dominated by family Columbidae. From the total species found, it could be classified into 32 families and 28 species including the endemic bird species. Seven bird species have been obtained from the mistnet method and among them, four species were found as endemic species. They were Dark-eared Myza (Myza celebensis celebensis), Matinan Blue Flycatcher (Cyornis sanfordi), Speckled Boobook (Ninox punctulata), and Sulawesi Leaf-warbler (Phylloscopus sarasinorum nesophilus).